2013
DOI: 10.1097/wnr.0b013e3283630126
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-suppressive effects of miR-29c on gliomas

Abstract: Although miR-29c has been shown to be expressed less in various kinds of solid cancers, its expression pattern and tumor-suppressive effects in gliomas remain largely unknown. In this study, we detected miR-29c in 10 nontumoral brain tissues and 60 gliomas of various grades and found that its labeling indexes were significantly lower in gliomas (53.7% for the nontumoral brain tissues, and 18.9, 5.5, and 1.8% for the WHO grade I-II, grade III, and grade IV glioma groups, respectively). We then overexpressed miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…The anti-glioma effects of some miR-29 family members as well as the related targets such as CDK6, MMP-2 and VEGF have been reported in several GBM cell lines [8,15]. We herein reconfirmed that all miR-29 family members effectively halted the proliferation, migration and invasion of U87MG cells and induced their apoptosis.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The anti-glioma effects of some miR-29 family members as well as the related targets such as CDK6, MMP-2 and VEGF have been reported in several GBM cell lines [8,15]. We herein reconfirmed that all miR-29 family members effectively halted the proliferation, migration and invasion of U87MG cells and induced their apoptosis.…”
Section: Discussionsupporting
confidence: 69%
“…The mature members of human miR-29 family, including miR29a-c, are expressed at aberrantly low levels in a variety of tumors including GBM [2][3][4][5][6][7][8]. Increasing evidence associates low miR29s expression with tumorigenesis and progression, indicating the tumor suppressive nature of these miRNAs.…”
Section: Introductionmentioning
confidence: 99%
“… 9 MiR-29c is a member of the miR-29 family, and has been reported to be deregulated in many different types of cancer. 10 12 MiR-29c is frequently silenced or downregulated in many kinds of cancers, including hepatocellular cancer, 13 , 14 nasopharyngeal cancer, 15 glioma, 16 , 17 gastric cancer, 18 , 19 bladder cancer, 20 and colorectal cancer, 21 and in those cancers, miR-29c usually has tumor-suppressive effects, while the expression levels of miR-29c in osteosarcoma tissues and patients’ sera are all significantly higher than those in normal controls. 22 In PC, recent reports have shown that miR-29c suppresses PC liver metastasis in a nude mouse model and affects patient survival, 23 and reduction of miR-29c enhances PC cell migration and stem cell-like phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…Nguyen et al ( 18 ) found that low levels of miR-29c were associated with the progression of melanoma, and Wang et al ( 19 ) identified an inhibitory role in hepatocellular carcinoma. Other investigations have revealed that miR-29c is involved in leukemia ( 20 ), glioma ( 21 ), bladder cancer ( 22 ) and nasopharyngeal ( 23 ) and gastric carcinoma ( 24 ). Taken together, it has become apparent that a common feature of tumorigenesis is the downregulation of miR-29c, and that the presence of miR-29c inhibits tumor cell growth, which may be indicative of improved prognosis.…”
Section: Introductionmentioning
confidence: 99%